Calibrated color measurement of cashmere using a novel computer vision system. (November 2021) - Heng, Chong; Shen, Hua; Wang, Fumei; Chen, Yufeng
Highlights: CVS, an alternative method of manual testing, was utilized to test cashmere color. Cashmere color testing condition was determined to standardize the measurement. A calibrated color conversion model used for cashmere color testing was proposed. The categories of cashmere could be objectively determined by the present work. Variation coefficients of color was obtained from CVS instead of a spectrophotometer. Abstract: Color of cashmere fiber is a key component of textile quality inspection. However, the inspection of cashmere color was determined by human vision system, which was less accuracy and time-consuming. Computer vision system (CVS) is considered as a promising technique to objectively and precisely test color. In the present work, a novel color measurement system for cashmere was proposed. Totally 29 cashmere samples with different color were adopted as standard samples to calibrate color conversion model. The correlation coefficient of L, a, b values between the two systems was separately calculated high to 0.99, 0.96 and 0.93 for the whole samples. The proposed method was further validated by other 15 samples, indicating the accuracy of the novel CVS. Besides, due to the high accuracy and strong representativeness of the new method, the categories of cashmere, which were normally tested by subjective visual assessment, could be determined by the present results.